Electric field tunable electronic structures and ultrahigh power conversion efficiency of BC6N/MoSe2 van der Waals heterostructure: A promising material for high-efficiency solar cell applications - Xie, You; Jiang, Ning-Ning; Han, Wei; Wang, Su-Fang; Chen, Li-Yong; Jin, Xin-Wen; Chen, Zheng-Yong; Xiao, Xiao-Sa; Zhou, Zi-Xuan; Song, Yu-Ling (The Journal of physics and chemistry of solids, 2024)
A novel BC6N/MoSe2 van der Waals heterostructure (vdWH) was fabricated by stacking monolayer BC6N onto monolayer MoSe2. The structural stability, electronic structure, optical properties, and power conversion efficiency (PCE) of the BC6N/MoSe2 vdWH were systematically investigated using first-principles calculations and by considering the effects of electric fields. The results indicated that the stable BC6N/MoSe2 vdWH has an indirect band gap of 1.84 eV, and exhibits a type II band alignment which is not affected by external electric fields. Additionally, the band gap of BC6N/MoSe2 decreased linearly with increasing intensity of the electric field, and the maximum band gap was 1.88 eV under an electric field of −0.05 V/Å. The optical absorptivity of the BC6N/MoSe2 vdWH increased in the visible region, with the highest optical absorptivity (23.1 %) observed in the violet region. The BC6N/MoSe2 vdWH displayed an ultrahigh PCE (22.9 %), which reached 23.6 % under an electric field of −0.05 V/Å. The PCE decreased with increasing intensity of the electric field, but was still high (19.1 %) under an electric field of 0.2 V/Å. The optimal optical absorptivity and ultrahigh and tunable PCE of the BC6N/MoSe2 vdWH indicate its great potential for application as high-efficiency solar cell materials. [Display omitted] •Developed a novel BC6N/MoSe2 van der Waals heterostructure with a band gap of 1.84 eV.•BC6N/MoSe2 exhibits type-II band alignment independent of an applied external electric field.•BC6N/MoSe2 has a strong optical absorptivity of 23.1 % in the violet region.•BC6N/MoSe2 has an ultrahigh PCE (22.9 %), which can reach 23.6 % under a −0.05 V/Å electric field.•The electronic structure and PCE of BC6N/MoSe2 can be modulated using an electric field.